Removal of the Black race coefficient from the estimated glomerular filtration equation improves transplant eligibility for Black patients at a single center. Issue 2 (21st October 2021) - Hoenig, Melanie P.; Mann, Alison; Pavlakis, Martha
Abstract: Race is a social construct that cannot be measured, can be used imprecisely and may contribute to disparities in kidney transplant access for Black patients. At Beth Israel Deaconess Medical Center, we dropped the Black race coefficient in the estimated glomerular filtration rate (eGFR) report in 2017. We conducted a quality improvement project to examine the impact of this change. Before the change, only 26% of our Black patients were listed for preemptive transplant compared to 70% of White patients. Since the change, we found a steady increase in the percentage of Black patients listed before starting dialysis. The average eGFR at listing prior to 2017 was significantly lower in Black patients but after, there was no longer a significant difference. Nine patients "gained" an average of 457 days of wait time directly related to discarding the Black race coefficient. Increased time on the list prior to dialysis initiation allows for evaluation of potential live donors and improves the possibility of a pre‐emptive live or deceased donor transplant and allows for a shorter period on dialysis before transplant. In this single center initiative, we demonstrate the benefit of discarding race from the eGFR report for Black patients awaiting kidney transplantation.